Modulated interlayer charge transfer dynamics in a monolayer TMD/metal junction. Issue 2 (13th December 2018) - Zhang, Linglong; Yan, Han; Sun, Xueqian; Dong, Miheng; Yildirim, Tanju; Wang, Bowen; Wen, Bo; Neupane, Guru Prakash; Sharma, Ankur; Zhu, Yi; Zhang, Jian; Liang, Kun; et al.
Abstract : The interlayer interactions and coupling of mTMD–metal junction determine the performance of the corresponding optoelectronic devices. Abstract : The performance of optoelectronic devices based on monolayer transition-metal dichalcogenide (mTMD) semiconductors is significantly affected by the contact at the mTMD–metal interface, which is dependent on interlayer interactions and coupling. Here, we report a systematic optical method to investigate the interlayer charge transfer and coupling in a mTMD–metal heterojunction. Giant photoluminescence (PL) quenching was observed in a monolayer MoS2 /Pd (1L MoS2 /Pd) junction which is mainly due to the efficient interlayer charge transfer between Pd and MoS2 . 1L MoS2 /Pd also exhibits an increase in the PL quenching factor ( η ) as the temperature decreases, due to a reduction of the interlayer spacing. Annealing experiments were also performed which supported interlayer charge transfer as the main mechanism for the increase of η . Moreover, a monolayer MoS2 /Au (1L MoS2 /Au) junction was fabricated for engineering the interlayer charge transfer. Interestingly, a narrowing effect of the full width at half maximum (FWHM) was encountered as the junctions changed from 1L MoS2 /SiO2 → 1L MoS2 /Au → 1L MoS2 /Pd, possibly originating from a change of the doping level induced weakening of exciton-carrier scattering. Our results deepen the understanding of metal–semiconductor junctions for further exploring fundamental phenomena and enabling high-performance devices using mTMD–metal junctions.